Di-nitrogen fixation at the early and late growth stages of soybean - Raphael Lemes Hamawaki (Acta Scientiarum: Agronomy, 2018)
Soybean derives a significant portion of the required nitrogen (N) from the symbiosis with rhizobia bacteria. However, information on the available genetic variation for N2 fixation capacity in different growth stages of soybean is limited. The objective of this study was to investigate the N2 fixation capacity of 22 soybean lines compared with that of non-nodulating and supernodulating checks at the early and late growth stages and identify the most informative traits for selection. Two cycles of greenhouse experiments were carried out to estimate the percentage of N derived from the atmosphere (%Ndfa) as well as 10 different traits related to N2 fixation. The results showed that %Ndfa was significantly different among the lines at the early and late growth stages. SPAD readings showed the highest correlation with the early N2 fixation, whereas shoot dry weight with the late N2 fixation. Early and late %Ndfa could be used to select superior lines for N2 fixation and study the underlying physiological and molecular mechanism.